The seismic cycle at subduction thrusts: 2. Dynamic implications of geodynamic simulations validated with laboratory models. Issue 4 (25th April 2013) - van Dinther, Y.; Gerya, T. V.; Dalguer, L. A.; Corbi, F.; Funiciello, F.; Mai, P. M.
Abstract : [1] The physics governing the seismic cycle at seismically active subduction zones remains poorly understood due to restricted direct observations in time and space. To investigate subduction zone dynamics and associated interplate seismicity, we validate a continuum, visco‐elasto‐plastic numerical model with a new laboratory approach (Paper 1). The analogous laboratory setup includes a visco‐elastic gelatin wedge underthrusted by a rigid plate with defined velocity‐weakening and ‐strengthening regions. Our geodynamic simulation approach includes velocity‐weakening friction to spontaneously generate a series of fast frictional instabilities that correspond to analog earthquakes. A match between numerical and laboratory source parameters is obtained when velocity‐strengthening is applied in the aseismic regions to stabilize the rupture. Spontaneous evolution of absolute stresses leads to nucleation by coalescence of neighboring patches, mainly occurring at evolving asperities near the seismogenic zone limits. Consequently, a crack‐, or occasionally even pulse‐like, rupture propagates toward the opposite side of the seismogenic zone by increasing stresses ahead of its rupture front, until it arrests on a barrier. The resulting surface displacements qualitatively agree with geodetic observations and show landward and, from near the downdip limit, upward interseismic motions. These are rebound and reversed coseismically. This slip increases adjacent stresses, which are relaxed postseismically by afterslip and thereby produce persistent seaward motions. The wide range of observed physical phenomena, including back‐propagation and repeated slip, and the agreement with laboratory results demonstrate that visco‐elasto‐plastic geodynamic models with rate‐dependent friction form a new tool that can greatly contribute to our understanding of the seismic cycle at subduction zones. Key points: Geodynamic simulations with rate‐dependent friction capture seismic thrust cycle Spontaneous, stress‐driven, mainly crack‐like rupture may re‐rupture hypocenter GPS displacements capture inter‐, co‐, and postseismic features via afterslip